PENGARUH VARIASI JENIS ASAM TERHADAP RENDEMEN GELATIN DARI TULANG IKAN CAKALANG (Katsuwonus pelamis) - Ahmad Ridhay; Musafira Musafira; Nurhaeni Nurhaeni; Nurakhirawati Nurakhirawati; Nurul Bima Khasanah (KOVALEN: Jurnal Riset Kimia, 2016)
The research about “The Effect of Variation of the Type of Acid on Gelatine Yield from Cakalang Fish Bone (Katsuwonus pelamis)”. The aim of this research was to determine the higher gelatine rendament using various of type of acid. This research used Completely Randomized Design (CRD), each treatment was done in duplo.The acid variation in this research were Chloride, Sulphate, Phosphoric, Acetic, Oxalate and Citrate acid respectively. The result showed that the highest rendament was 14,658% at 5% of phosphoric acid. The analysis of the treatment has fulfilled the standard. Keywords : Gelatine, Cakalang fish bone, Isolate, Yield